DINAMIKA MASYARAKAT DAN BUDAYA DALAM PENDIDIKAN ISLAM - Drs. H Firdaus (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2016)
Society is a large or small group, consisting of some humans, who by or for itself concerned by groups and influence upon each other. Sociology is the science of society or science-Detention kemasya who study humans as a group or community members, (not as individuals regardless of class or community).